1998
DOI: 10.1006/viro.1998.9054
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Analysis of the Herpes Simplex Virus Type 1 UL12 Gene: Correlation of Deoxyribonuclease Activityin Vitrowith Replication Function

Abstract: Although the product of the UL12 gene of herpes simplex virus type 1 (HSV-1) has been shown to possess both exonuclease and endonuclease activities in vitro, and deletion of most of the gene within the viral genome results in inefficient production and maturation of infectious virions, the function of the deoxyribonuclease (DNase) activity per se in virus replication remains unclear. In order to correlate the in vitro and in vivo activities of the protein encoded by UL12, mutant proteins were tested for nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…Intriguingly, a previous study had shown that two mutations in the N-terminal regions of UL12 and UL12.5 that are absent from UL12 M185 inactivate detectable nuclease activity in vitro (23). Taken together, these data raised the possibility that UL12 M185 lacks enzymatic activity and, by extension, that the nuclease activity of UL12.5 is not required for mtDNA depletion.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Intriguingly, a previous study had shown that two mutations in the N-terminal regions of UL12 and UL12.5 that are absent from UL12 M185 inactivate detectable nuclease activity in vitro (23). Taken together, these data raised the possibility that UL12 M185 lacks enzymatic activity and, by extension, that the nuclease activity of UL12.5 is not required for mtDNA depletion.…”
mentioning
confidence: 83%
“…The L150K mutation was introduced using a modified site-directed mutagenesis protocol (25) with primers F4 and R3. The ⌬N mutation (deletes residues W128 to R148 [23]) and the ⌬MLS mutation (deletes residues R188 to R212 [10]) were both introduced using a QuikChange XL site-directed mutagenesis kit (Stratagene) with primers F5 and R4 and primers F6 and R5, respectively. The ⌬C mutation (deletes residues P578 to R626 [23]) was created by PCR using primers F2 and R6.…”
Section: Cells and Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, analysis of replicating concatemeric DNA suggests that in the absence of AN the replicative intermediates have a more complex structure with an increased frequency of branches (Martinez et al, 1996a), whilst structural abnormalities have also been detected in the genomes of progeny virions (Porter & Stow, 2004). Taken together, these observations suggest a possible role for AN in the resolution of recombination intermediates prior to DNA packaging, and this model is supported by the observation that the nuclease function, per se, of the UL12 protein is necessary for efficient replication (Goldstein & Weller, 1998b;Henderson et al, 1998). It can be envisaged that failure to correctly resolve branched structures could have an indirect impact upon DNA synthesis and the assembly of the infectious virus particle.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies also indicated that similar modes of action are present in herpesviral DNases purified from different sources [14,15]. A structure-function analysis of the herpesviral DNase showed that mutations at the N-terminus of gammaherpesvirus (Epstein-Barr virus ; EBV) eliminate its exonuclease activity [16] ; however, other studies indicated that the N-terminus of herpes simplex virus type 1 (HSV-1) DNase might not have a role in its enzymic activity [17]. Goldstein and Weller [18] showed also that Abbreviations used : DEPC, diethyl pyrocarbonate ; EBV, Epstein-Barr virus ; HSV-1, herpes simplex virus type 1 ; PRV, pseudorabies virus ; UL12, alkaline nuclease.…”
Section: Introductionmentioning
confidence: 99%